Legg-Calvé-Perthes disease: Diagnostics and contemporary treatment - Vukašinović Zoran (Srpski Arhiv za Celokupno Lekarstvo, 2008)
Legg-Calvé-Perthes disease represents avascular necrosis of the femoral head in a growing child. It commonly affects children aged 2-14 years, mostly boys, and has familiar pattern. The etiology of this disease is unknown. It is based on avascular necrosis due to variations of the femoral head vascular supply, trauma, coagulation of endocrine disturbances. The disease presents with limping and pain localized in the hip with projection to thigh and knee, frequently accompanied by the limitation of abduction and internal rotation, as well as slight limitation in flexion of about 20 degrees. Plain radiography is most informative additional diagnostic procedure, enabling assessment of the stage of disease, containment of the femoral head within the acetabulum, acetabular coverage and the extent of disease. Main treatment goal is obtaining the spherical congruity of the hip joint. This can be achieved by abduction bracing, varization femoral osteotomies and various innominate osteotomies (sometimes combined with femoral osteotomies). Children younger than four years of age, with minimal femoral head involvement, do not need any treatment. These children with a larger involvement, older than four years of age, with possible containment in hip abducion, should be treated by one of the following procedures: Salter innominate osteotomy, Salter innominate osteotomy with femoral shortening, or triple pelvic osteotomy. The patients with containment of the hip is not possible in abduction (related to subluxation and femoral head crush), should be treated by Chiari pelvic osteotomy.